INTEGRATING ACCOUNTING INFORMATION SYSTEMS AND ENTERPRISE RISK MANAGEMENT FOR REAL-TIME FINANCIAL RISK MONITORING - Hossen, Munkashir (International Journal of Accounting Innovation, 2025)
Objective: This study aims to examine the strategic integration of Accounting Information Systems (AIS) and Enterprise Risk Management (ERM) as a mechanism for strengthening real-time financial risk monitoring and improving organizational decision-making in dynamic financial environments. Method: The study adopts a conceptual and analytical review approach by synthesizing relevant literature on AIS functionality, ERM frameworks, cybersecurity risks, and digital risk governance. Key themes related to system integration challenges, risk control mechanisms, and governance practices are systematically analyzed to develop an integrated perspective. Results: The findings indicate that AIS–ERM integration enables organizations to shift from reactive financial management toward proactive and predictive risk identification through accurate data processing, real-time monitoring, and advanced analytics. However, implementation challenges persist, including legacy system incompatibility, cybersecurity threats, human error, and organizational resistance. The adoption of best practices—such as encryption, access control, continuous monitoring, incident response planning, and leadership-driven change management—significantly enhances system reliability and risk mitigation effectiveness. Novelty: This study highlights the strategic value of aligning transactional accuracy with enterprise-wide risk governance by emphasizing predictive analytics, customizable dashboards, and risk-aware organizational culture as critical enablers of modern financial governance.